Analysis of the times involved in processing and communication in a lower limb simulation system controlled by SEMG. (April 2016) - Profumieri, A.; Bonell, C.; Catalfamo, P.; Cherniz, A.
Abstract: Virtual reality has been proposed for different applications, including the evaluation of new control strategies and training protocols for upper limb prostheses and for the study of new rehabilitation programs. In this study, a lower limb simulation environment commanded by surface electromyography signals is evaluated. The time delays generated by the acquisition and processing stages for the signals that would command the knee joint, were measured and different acquisition windows were analysed. The subjective perception of the quality of simulation was also evaluated when extra delays were added to the process. The results showed that the acquisition window is responsible for the longest delay. Also, the basic implemented processes allowed for the acquisition of three signal channels for commanding the simulation. Finally, the communication between different applications is arguably efficient, although it depends on the amount of data to be sent.